The Influence of the Hyaluronic Acid Gel on the Postoperative Sequelae following Surgical Removal of the Impacted Mandibular Third Molar in Comparison with the A-PRF: A Randomized Controlled Trial - Thoulfokar Shokor Al-Saadi; Ahmed Fadhel Al-Quisi (International Journal of Biomaterials)
One of the most common procedures in oral surgery is the removal of impacted mandibular third molars, often followed by pain, swelling, alveolitis, and trismus. Purpose. To compare the outcomes of the intrasocket application of 1% hyaluronic acid oral gel (HA) and advanced platelet-rich fibrin (A-PRF) on the expected postoperative complications, pain, swelling, and trismus follow the surgical extraction of the impacted mandibular third molar. Material and Methods. A randomized controlled trial was conducted at the Oral and Maxillofacial Surgery Unit, Dental Teaching Hospital. Healthy patients who required surgical removal of the impacted mandibular third molar were divided randomly into three groups. The extraction site of the group (A) patients remained without the addition of any material, just suturing of the wound with simple interrupted sutures, while in group (B) patients, the extraction site was filled with 1 cc of 1% hyaluronic acid gel (periokin®), and in group C patients, the extraction site was filled with A-PRF. Results. Sixty-six eligible patients participated in this study; both hyaluronic acid gel 1% (periokin®) and advanced platelet-rich fibrin showed a significant reduction in pain, swelling, and trismus on the 1st, third, and seventh postoperative days when compared to the control group, while the comparison between HA and A-PRF showed no significant differences except for the pain on the third postoperative day. There was a significant pain decrease in the A-PRF group than HA group. Conclusion. Intrasocket application of 1% hyaluronic acid gel (periokin®) or advanced platelet-rich fibrin can be an effective primary way to significantly reduce postoperative pain, trismus, and edema compared to the control group following mandibular third molar surgery.